CAPITAL STRUCTURE: EARNING AND THE PERFORMANCE OPTIONS IN SMALL AND MEDIUM SCALES ENTERPRISES - Kehinde, James Sunday (European Scientific Journal, ESJ, 2013)
The study examined the relationship that exist between the capital structure mix of the SMEs and the overall performance of the firm over the year s, poor combination of debt-equity finance has been the bane of small and medium scale enterprises (SMEs) in Nigerian. The study made use of questionnaire a survey method for data collection and chi-square a non-parametric method for data analysis. The study revealed that most SMEs have an all equity finance structure and has a less debt finance to equity finance. It also revealed that the earning, survival and growth of the SMEs is strongly influence by the capital structure mix.It was recommended that the government should design a homegrown and SMEs friendly debt financing structure and managers of SMES should also seek professional advice when approaching financial institutions for debt finance.